2020
DOI: 10.20944/preprints202003.0434.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Crucial Aspects of the Management of Solid Organ Transplant Patient with COVID-19: A Narrative Review

Abstract: Many centers worldwide raised the concern that immunocompromised patients for solid organ transplantation may be at high risk of developing a severe respiratory disease by COVID-19. Currently, there are no specific data on the COVID-19 in patients with generalized immunosuppression and transplantation.In this narrative review, we reported the main data of COVID-19 in patients with solid organ transplantation presented in the literature. The aim is to elaborate a strategy for tailored management, from diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…Their adequate clinical course suggests that in patients with this type of transplant the disease has a similar presentation to non-transplanted patients. 59 It should be noted that in a series of seven cases 60 (two liver, three kidney, one lung and one heart) an initial attenuated inflammatory response was evident, suggesting that although patients with transplant immunosuppression may have higher susceptibility to SARS-CoV-2 infection, their clinical course could be similar to that of immunocompetent patients.…”
Section: Current Evidence Of Conditions Associated With Immunosuppresmentioning
confidence: 94%
See 1 more Smart Citation
“…Their adequate clinical course suggests that in patients with this type of transplant the disease has a similar presentation to non-transplanted patients. 59 It should be noted that in a series of seven cases 60 (two liver, three kidney, one lung and one heart) an initial attenuated inflammatory response was evident, suggesting that although patients with transplant immunosuppression may have higher susceptibility to SARS-CoV-2 infection, their clinical course could be similar to that of immunocompetent patients.…”
Section: Current Evidence Of Conditions Associated With Immunosuppresmentioning
confidence: 94%
“…We highlight the study of a case series, 59 two heart and kidney transplants and one liver (paediatric population). The heart transplant patients were confirmed by PCR to be infected, one of them was 51 years old, came with immunosuppression with tacrolimus 2 mg per day and mycophenolate 1 g per day, and attended consultation for fever, fatigue and liquid stools, with characteristic findings of SARS-CoV-2 infection on chest tomography.…”
Section: Current Evidence Of Conditions Associated With Immunosuppresmentioning
confidence: 99%
“…However, the study is observational and not a blinded randomized clinical trial (RCT) and both groups were also treated with multiple non-protocolized drugs: two thirds of the patients were given high-dose steroid, one third were given intravenous immunoglobulin, one third an interleukin-6 (IL-6) inhibitor, and all patients were given hydroxychloroquine, thus making it difficult to draw definite clinically conclusions from these interesting observations from Rodriguez-Cubillo et al 15 The transplantation society currently recommends close attention to patients with medication-induced lymphopenia, but no specific instructions on antirejection regimen exist because of the current lack of evidence. 16 Romanelli et al 17 have suggested that clinicians must consider pausing immunosuppressants in transplanted patients with COVID-19, which is a common strategy in transplanted patients with infections. This suggestion may in part be based on data from the epidemic of Middle East respiratory syndrome (MERS) as some case reports of kidney transplant recipients infected with MERS died.…”
Section: Introductionmentioning
confidence: 99%
“…The transplantation society currently recommends close attention to patients with medication‐induced lymphopenia, but no specific instructions on antirejection regimen exist because of the current lack of evidence 16 . Romanelli et al 17 have suggested that clinicians must consider pausing immunosuppressants in transplanted patients with COVID‐19, which is a common strategy in transplanted patients with infections. This suggestion may in part be based on data from the epidemic of Middle East respiratory syndrome (MERS) as some case reports of kidney transplant recipients infected with MERS died 18,19 …”
Section: Introductionmentioning
confidence: 99%
“…It is generally admitted that immunosuppressive therapy in transplanted patients modulates humoral and cell-mediated immunity increasing the risk of severe infection when exposed to viruses ( 97 ). In regard to this idea, some authors suggested pausing immunosuppressant drugs as a precaution in transplanted patients found positive for SARS-CoV-2 ( 98 ). Yet, it was also reported that transplanted patients have not been found more susceptible to viral infections and severe forms of COVID-19 than the general population ( 99 101 ), which begs questions about the relationship between CsA treatment and COVID-19.…”
Section: Is There a Perspective For Csa Repurposing In Covid-19?mentioning
confidence: 99%